PENERAPAN BOARDGAME: ULAR TANGGA SEBAGAI MEDIA EDUKASI KESEHATAN GIGI DAN KEBERSIHAN DIRI PADA SISWA TAMAN KANAK-KANAK - Urrahman, Dhiya; Baiquni, Fahmi; Salsabila, Salma; Sabarno, Nur Amalia Mardyani (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2023)
Health education in a fun way is very important, especially for children at kindergarten age. Learning through games can make the learning process more interactive and interesting. This activity aims to increase kindergarten students' knowledge and awareness of dental health and personal hygiene through the application of a snakes and ladders board game. Several studies have shown that fun learning methods such as games can increase children's interest and understanding. In this activity, the snakes and ladders board game was modified to include educational elements related to dental health and personal hygiene. Through this game, children are taught how to maintain dental hygiene, the importance of brushing their teeth regularly, and the steps to maintain personal hygiene. This activity was carried out in the form of interactive teaching at PKK 8 Mangir Kindergarten. The evaluation results showed an increase in children's knowledge and hygiene behaviour, as well as high enthusiasm from the participants. It is hoped that this activity can become a broader health education model at the early childhood education level.